Pengaruh Gangguan "Circadian" Terhadap Struktur Histologik Testis dan Ovarium Tikus Putih (Rattus norvegicus) - Daryanto, Daryanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1988)
The effect of the total solar eclipse on the testicular and ovarian tissues of the albino rats has been investigated.Thirty adult male and female albino rats, Lembaga Makanan Rakyat (LMR) strain, were used in this investigation, and consisting of 15 male and 15 female albino rats and divided into three main groups.The first group, consisting of 5 male and 5 female albino rats were used as control group and to be decapitated one hour before the total solar eclipse occurred. The second group, consisting of 5 male and 5 female albino rats were used as a treatment group, which experienced a total solar eclipse and to be decapitated exactly when the eclipse finished. The third group consisting of 5 male and 5 female albino rats were used as a second control group, and to be decapitated one hour after the total solar eclipse finished.The results of this investigation revealed that there is no significant differences in the structure and function of testicular tissues as well as of ovarian tissues of the albino rats.Key Words: circadian rhythm - total solar eclipse - testis - ovarium - photoperiodicity